The perspective of professional caregivers working in generalist palliative care on 'good dying': An integrative review. (January 2022) - Lang, Alexander; Frankus, Elisabeth; Heimerl, Katharina
Abstract: In today's industrial societies, many people die receiving professional care. Although specialist palliative and hospice care have often been identified as ideal care approaches to promote good dying, more people die receiving generalist palliative care. This integrative review examines how professional caregivers providing generalist palliative care in hospitals, nursing or private homes define good dying. Furthermore, through comparative analysis of existing empirical studies, it explores conceptual aspects in researching good dying that better reflect the social complexity of this phenomenon. Three databases (Scopus, MEDLINE, and CINAHL) were searched for peer-reviewed studies published between January 2000 and April 2020. Studies were selected if they presented original empirical findings from qualitative or quantitative studies on the perspective of professional caregivers in generalist palliative care (nurses, physicians, surgeons, clergy, and other staff) on good dying or related concepts (e.g., good death, dignity in dying, or quality of life at the end of life). 42 studies were included in the review. They identified good dying as expected, accepted and prepared dying, as free from pain and suffering, as socially embedded, as being at peace with one's life and situation, as supported with individualised and holistic care, as based upon professional cooperation and communication, and as in a peaceful and private environment. The paper concludes that the perspective of professional caregivers in generalist palliative care shares many elements of good dying with societal and specialist palliative care discourses around good dying. Through comparing the different studies, the review found that studies that explicated who benefitted from ideals and practices of good dying, questioned the dichotomous categorisation of good/bad dying, or discussed the compatibility of elements of good dying, provided more nuanced perspectives on this topic. Thus, the review calls for a more systematic analysis of these aspects in research of good dying. Highlights: Good dying in generalist palliative care (PC) is similar to that in specialised PC. Preparation, painlessness, companionship, peace & individualised care are important. Studies rarely explicitly address who benefits from practices related to good dying. Tensions between different good dying elements are hardly ever a topic. Seemingly dichotomous relationship between good and bad dying needs scrutiny.